Impact of level 2 automation and ADHD symptomatology on young drivers' attention maintenance. (April 2023) - Parker, Jah'inaya; Wang, Meng; Ojuri, Beatrice; Roberts, Shannon C.; McDermott, Jennifer; Fisher, Donald L.
Highlights: Research on young drivers' glance behavior while using automation is limited. Vehicle automation led to longer glances off the road. There was no effect of ADHD symptomatology on glance behavior. Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is a common mental disorder that affects drivers' attention maintenance skills. Vehicle automation is another factor that has an increasingly important effect on drivers' attention or concentration level during driving. This driving simulator study aimed to investigate how drivers' glance behavior changed under different levels of vehicle automation and according to high or low ADHD symptomology. During the drive, participants were asked to complete a map task on a tablet while their glance behavior was recorded. Results imply that the participants tend to have a longer mean off-road glance duration and a larger long off-road glance ratio when they were under the L2 automation level compared to manual mode. ADHD symptomatology and the interaction between ADHD and vehicle automation were not found to be significant. These findings indicate that vehicle automation negatively impacts drivers' attention maintenance skills. Future work would consider more kinds of secondary tasks that can assess the participants' attention maintenance skills from various aspects.